A manifestation of non-hydrodynamic factors in steady-state conditions of friction / Tareq M.A. Al-quraan - M.A. Al-quraan, Tareq (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This study considers the mechanisms of forming the thickness of the lubricant layer with mineral and synthetic oils under a gradual increase in the rolling speed. The determined regularities reveal non-Newtonian properties acquired by the oils at high contact loads and low rolling rates. An increase in the speed and temperature is found to restore Newtonian properties of the oils. The kinetics of forming the lubricating layer can depend on the effective viscosity of oils in contact, although this parameter does not always correlate with viscosity of oils in atmospheric conditions. A delayed impact of pressure on an effective viscosity is determined at a stronger manifestation of viscoelastic properties of oils. The study reveals the existence of threshold changes in the effective viscosity at high contact loads due to the model of a free volume between the components of the lubricant.